Realization of the F0 Parameter of German Spontaneous Speech: A Case Study of Two Male Speakers of Different Ages - Alexandra Nimas Devianne Inaz Christie; Agus Ridwan (Jurnal Lingua Idea, 2026)
This study investigates age-related differences in fundamental frequency (F0) realization and intonation patterns in semi-spontaneous German speech produced by two male speakers aged 12 and 24 years. Previous studies on German acoustic phonetics have predominantly examined F0 patterns in controlled or read speech, or in adult speakers, while studies combining F0 analysis with semi-spontaneous speech and speakers from different age groups remain limited. This study addresses this gap by examining how age influences F0 realization and intonational organization in naturally occurring spoken responses. The data consist of five semi-spontaneous utterances produced by both speakers in the German To Go series on the Coffee Break Languages YouTube channel. The utterances are categorized as semi-spontaneous because they are produced as spoken responses within predetermined topics and communicative contexts rather than from scripted reading tasks. Acoustic analysis was conducted quantitatively using Praat to extract F0 values, while prosodic segmentation employed the Intonational Phrase (IP) framework to identify intonation contours and pitch reset phenomena. The results show that the 12-year-old speaker consistently produces higher average F0 values and a wider pitch range than the 24-year-old speaker. In contrast, the adult speaker demonstrates smoother F0 contours and more stable intonation development across utterances. The younger speaker exhibits more frequent pitch fluctuations and more dynamic F0 movements, indicating age-related differences in prosodic realization. These findings contribute to the study of German acoustic phonetics by demonstrating how age affects F0 realization and IP-based intonation patterns in semi-spontaneous speech. The study is limited by the small number of speakers and utterances analyzed; therefore, future research should include larger speaker populations and additional prosodic parameters to obtain a more comprehensive understanding of age-related prosodic variation in German speech.